Policy risk in action: Pension reforms and social security wealth in Hungary, Czech Republic and Slovakia - Libor Dušek; Juraj Kopecsni (Charles University in Prague, Institute of Economic Studies (IES), 2008)
We provide evidence on the policy risk of social security in Hungary, Czech Republic and Slovakia by computing the changes in the social security wealth induced by the pension reforms undertaken since the 1990s. Methodologically we follow upon McHale' (2001) study of selected reforms in G7 countries. However, as we measure the differential impact of the reform on workers of different genders, ages, and levels of education, we are able to capture the aggregate, intergenerational, and intragenerational aspects of the policy risk. Overall, the paper documents that also a pay-as-you-go system is not a secure source of retirement income since pension reforms do change the future contributions and benefits in different directions for different workers, and the magnitude of the reductions in social security wealth sometimes exceeds several years' worth of the workers' earnings.
Keywords: H55; G32; P35; 330; social security; policy risk; pension reforms; Soziale Sicherung; Rentenreform; Politische Stabilität; Risiko; Ungarn; Tschechische Republik; Slowakei